Holy Word : the paradigm of New Testament formation - Baird, J. Arthur (Joseph Arthur) (Journal for the study of the New Testament. Supplement series ;, 2002)
J. Arthur Baird is the author of several important books in New Testament studies, his best known perhaps being his Audience Criticism and the Historical Jesus. At his untimely death, he left a nearly complete manuscript, now published here. In this timely and relevant manuscript, Baird offers first a critical introduction to the historical paradigm, pointing out its limitations in terms of tracing the paradigm of New Testament formation. He then traces this development himself, beginning with the starting point of the Holy Word and noting its development through the context, theological inter.